2020
DOI: 10.1101/2020.03.11.986943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cerebellar Purkinje cells can differentially modulate coherence between sensory and motor cortex depending on region and behavior

Abstract: Coherence among sensory and motor cortices is indicative of binding of critical functions in perception, motor planning, action and sleep. Evidence is emerging that the cerebellum can impose coherence between cortical areas, but how and when it does so is unclear. Here, we studied coherence between primary somatosensory (S1) and motor (M1) cortices during sensory stimulation of the whiskers in the presence and absence of optogenetic stimulation of cerebellar Purkinje cells in awake mice. Purkinje cell activati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Specifically, neural activity in the cerebellum represents the coherence of neural oscillations between the hippocampus and prefrontal cortex [93], and inhibition of the cerebellar cortex disrupts this coherence and may decrease performance in a memory task [94]. Interestingly, this role of the cerebellum in modulating coherence of multiple brain regions is not restricted to cognitive function, as excitation of Purkinje cells also disrupts phase coherence between the sensory and motor cortices during whisker stimulation [95]. Thus, while these functional studies do not confirm that disruption of cerebellar development causes early-onset cognitive, social, or language impairments directly observed in ASD, they provide compelling evidence that the cerebellum directly modulates brain-wide neural networks involved in highly complex cognitive tasks.…”
Section: Disruptions In Cerebellar Function Lead To Social and Cognitive Deficits In Micementioning
confidence: 99%
“…Specifically, neural activity in the cerebellum represents the coherence of neural oscillations between the hippocampus and prefrontal cortex [93], and inhibition of the cerebellar cortex disrupts this coherence and may decrease performance in a memory task [94]. Interestingly, this role of the cerebellum in modulating coherence of multiple brain regions is not restricted to cognitive function, as excitation of Purkinje cells also disrupts phase coherence between the sensory and motor cortices during whisker stimulation [95]. Thus, while these functional studies do not confirm that disruption of cerebellar development causes early-onset cognitive, social, or language impairments directly observed in ASD, they provide compelling evidence that the cerebellum directly modulates brain-wide neural networks involved in highly complex cognitive tasks.…”
Section: Disruptions In Cerebellar Function Lead To Social and Cognitive Deficits In Micementioning
confidence: 99%
“…We hypothesized that the cerebellum might play a critical role in processing the information required for stable HD cell activity patterns. Also, since the cerebellum is involved in temporal synchronization between distant structures (Lindeman et al, 2021;Liu et al, 2020;McAfee et al, 2019;Popa et al, 2013), we sought to examine the influence of the cerebellum on the coordination between different HD structures.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, experiments have shown that both the second and third mechanisms rely on cerebellar modulation of thalamic activity for effective somatomotor integration. In the lessobvious case of cortico-cortical communication between vS1 and vM1, synchronous rhythms between structures that promote this form of communication require an intact cerebellum (Popa et al, 2013;Lindeman et al, 2021). Using various methods to inhibit the cerebellar nuclei, it has been shown that cerebellar inactivation reduces the firing rate in motor thalamic neurons (Popa et al, 2013), decreases gamma-rhythmic coherence between vS1 and vM1 (Popa et al, 2013;Lindeman et al, 2021), and impairs the ability of animal to adapt whisking strategies appropriately in a changing sensory context (Proville et al, 2014).…”
Section: Sensorimotor Functionsmentioning
confidence: 99%